PENERAPAN TEORI ANTREAN UNTUK ANALISIS KINERJA SISTEM PELAYANAN DI GERBANG TOL GAYAMSARI - Yunanur Hanikmah; Sugito Sugito; Mustafid Mustafid (Program Studi Statistika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Muham, 2019)
Queue theory is a method that can be used to analyze the performance of a service system. This study aims to apply queue theory for analysis system performance’s size at the Gayamsari Toll Gate by using data obtained through observation. Then the analysis step starts with checking the steady state assumption, goodness of fit tests to data, determines thequeue model, simulates the queue model, and calculates system performance’s size. Based on analysis with Arena software, the results of the study obtained queue model with Beta distribution on the number of arrivals and the number of services data. From this model, it can be used to calculate the service system performance’s size at the Gayamsari Toll Gate.The result of this calculation include estimates of the waiting time and the number of vehicles in the system or queue. Beside that based on the result of performance’s size, it can be concluded that the service system at the Gayamsari Toll Gate is in good condition because it’s waiting time is less than half minute. Keywords: Queue, Beta Distribution, Performance’s Size